2014
DOI: 10.1016/j.bmc.2014.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Controlling substrate specificity and product regio- and stereo-selectivities of P450 enzymes without mutagenesis

Abstract: P450 enzymes (P450s) are well known for their ability to oxidize unactivated C-H bonds with high regio-and stereoselectivity. Hence, there is emerging interest in exploiting P450s as potential biocatalysts. Although bacterial P450s typically show higher activity than their mammalian counterparts, they tend to be more substrate selective. Most drug-metabolizing P450s on the other hand, display remarkable substrate promiscuity, yet product prediction remains challenging. Protein engineering is one established st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Co‐crystallization of 4‐F‐ l ‐tryptophan with TxtE should offer novel and detailed insights. On the other hand, substrate‐controlled regio‐selectivity has been observed in several P450 reactions . PikC hydroxylates both C12 and C10 of YC‐17 in pikromycin biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Co‐crystallization of 4‐F‐ l ‐tryptophan with TxtE should offer novel and detailed insights. On the other hand, substrate‐controlled regio‐selectivity has been observed in several P450 reactions . PikC hydroxylates both C12 and C10 of YC‐17 in pikromycin biosynthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we demonstrate a method for addressing this challenge that relies on a directing group distal to the site of functionalization and overrides steric or electronic effects inherent to the substrate with the ultimate goal of achieving a P450/directing group platform that can be broadly applied without requiring extensive protein engineering for each new substrate. While such a synthetic strategy using small molecule catalysts originates from the pioneering early studies by Breslow 14,15 and has been applied in recent efforts to achieve meta -functionalizations of arenes 16,17 , the architectural complexity and unique anchoring mechanism of biological catalysts provides what is perhaps the ideal platform for engineering directed reactions to functionalize remote and unactivated structural elements 18,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new strategy of substrate engineering has been explored (23,24), wherein anchoring/directing groups are chemically linked to nonsubstrate compounds. Initial studies demonstrated that the addition of these anchoring groups facilitates enzyme-substrate interactions and enables selective oxidation of C-H bonds in previously inaccessible substrates.…”
mentioning
confidence: 99%